Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

WilsonWorla

  • 3 years ago

The area of an ellipse is A = πab, but the perimeter cannot be expressed so simply: P≈ π(a+b)(3-(√(3a+b)(a+3b))/(a+b) ) prove that, when a=b=r, these become the familiar formulas for the area and perimeter of a circle

  • This Question is Closed
  1. agent0smith
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Try replacing all the b's with a. eg in the area: A = πab becomes \[A = πaa = πa^2 = \pi r^2 \] P will become: \[P≈ π(a+a)(3-(√(3a+a)(a+3a))/(a+a) ) \] now try simplifying that.

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy